Freedom of press in Malaysia — legal consideration / Rosli Kamaruddin - Kamaruddin, Rosli (Faculty of Law, 1987)
One of the most eloquent signs of a country's moral and spiritual strength is to be seen in a strong and effective Frees. It is the shop—window of literacy. It is the symbol of the free spirit. Ideally, it should be able to transmit information and independence opinions, be accessible to the whole community, practice “investigative reporting" and provide a forum for the exchange of thoughts. To function thus excellently, there must be a free flow of ideas unhampered by Government "guidance"; any control to ensure a sense of responsibility must be initiated by itself or a truly independent body. Generally, there can be said to be three modern theories of the Press. First, there is the totalitarian theory of the Press, under which, the press is an instrument for achieving unity of opinion and under which, therefore, objectively in news reporting is discourage. Under such a system, it may be proclaimed that the wishes of the people governed the society; the catch is that the people’s rulers determine the wishes of the people and use the press to “educate” the people as to that single will. The press exists as an arm of the state; ownership is public, criticism of the government as distinguished from party propaganda is forbidden; there is strict political surveillance and control.